2011
DOI: 10.1073/pnas.1012232108
|View full text |Cite
|
Sign up to set email alerts
|

SCARECROW-LIKE 3 promotes gibberellin signaling by antagonizing master growth repressor DELLA in Arabidopsis

Abstract: The diterpenoid phytohormone gibberellin (GA) controls diverse developmental processes throughout the plant life cycle. DELLA proteins are master growth repressors that function immediately downstream of the GA receptor to inhibit GA signaling. By doing so, DELLAs also play pivotal roles as integrators of internal developmental signals from multiple hormone pathways and external cues. DELLAs are likely nuclear transcriptional regulators, which interact with other transcription factors to modulate expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
314
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(336 citation statements)
references
References 51 publications
15
314
0
7
Order By: Relevance
“…S5). These characteristics are reminiscent to those reported for SCL3 Zhang et al, 2011), which were also observed under our experimental conditions ( Fig. 4B; Supplemental Fig.…”
Section: Seu Is An Upstream Activator Of Shr Scr and Scl3supporting
confidence: 89%
See 1 more Smart Citation
“…S5). These characteristics are reminiscent to those reported for SCL3 Zhang et al, 2011), which were also observed under our experimental conditions ( Fig. 4B; Supplemental Fig.…”
Section: Seu Is An Upstream Activator Of Shr Scr and Scl3supporting
confidence: 89%
“…SEU Mediates the Regulation of SCL3 Expression by GA Signaling SCL3 expression is induced by DELLA proteins and repressed by GA Zhang et al, 2011), which acts in conjunction with SHR and SCR to regulate the formation of MC . Because our results showed that SCL3 is epistatic to SEU, we next examined whether GA signals through SEU to repress SCL3 expression.…”
Section: Seu Is An Upstream Activator Of Shr Scr and Scl3mentioning
confidence: 99%
“…Moreover, GRAS proteins have been reported to form homodimers and heterodimers with other GRAS family members and this is likely important for their transcriptional regulation function (Itoh et al, 2002;Cui et al, 2007;Heo et al, 2011;Zhang et al, 2011;Gobbato et al, 2012;Murakami et al, 2013;Xue et al, 2015). Here, our structure of Os-SCL7 was determined in a dimer with helices A12, A79, and A69 at the dimer interface.…”
Section: Discussionmentioning
confidence: 96%
“…DELLA proteins lack a DNA binding domain; however, they function as transcription activators by interacting with INDETERMINATE Domain (IDD) proteins (Yoshida et al, 2014). In addition to interacting with IDDs, At-SCL3 can directly bind with its own promoter to regulate the expression in planta (Zhang et al, 2011). Mt-NSP1 can bind to the AATTT motif on the promoters, but Mt-NSP2 may have to associate with Mt-NSP1 for transcriptional regulation .…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factors that directly regulate the expression of GA3OX genes in Arabidopsis are only partially known (Hedden and Thomas, (Matsushita et al, 2007), SCARECROW-LIKE13 (Zhang et al, 2011), and SOMNUS (Kim et al, 2008), affects GA3OX1 and GA3OX2 expression, but there is no evidence for their binding to the promoter of the genes. Only FUS3 (Curaba et al, 2004) and DOF AFFECTING GERMINATION1 (Gabriele et al, 2010) have been shown to repress GA3OX1 and GA3OX2, respectively, by binding to the promoter of the regulated gene.…”
Section: Discussionmentioning
confidence: 99%